2019
DOI: 10.21147/j.issn.1000-9604.2019.03.13
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant hormone therapy after radical prostatectomy in high-risk localized and locally advanced prostate cancer: First multicenter, observational study in China

Abstract: Objective Potential of combined androgen blockade (CAB) has not been explored extensively in Chinese males with prostate cancer (PCa). Therefore, this study evaluated the 2-year prostate-specific antigen (PSA) recurrence rate and quality of life (QoL) in patients with high-risk localized and locally advanced PCa receiving adjuvant hormone therapy (HT) after radical prostatectomy (RP). Methods This prospective, multicenter, observational study conducted in 18 centers acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
8
1
Order By: Relevance
“…The CAB group demonstrated the least recurrence rates; however, the difference among groups was non-significant. [ 22 ] In addition, there were some differences between the present study and that of Ye et al . First, Ye et al enrolled N1M0 PCa.…”
Section: Discussioncontrasting
confidence: 88%
“…The CAB group demonstrated the least recurrence rates; however, the difference among groups was non-significant. [ 22 ] In addition, there were some differences between the present study and that of Ye et al . First, Ye et al enrolled N1M0 PCa.…”
Section: Discussioncontrasting
confidence: 88%
“…The formula of Dahuang Zhezhong pills (DHZCP) is from Jingui Yaolue complied by Zhang Zhongjing, the medical sage at the end of the Eastern Han dynasty. With the in-depth study of DHZCP in recent years, it is found that the drug has merits in tumor inhibition and adjuvant treatment [ 8 , 9 ]. However, no study has confirmed its efficacy in the adjuvant treatment after radical prostatectomy for early-to-mid prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims to report the prognosis of AR-V7 positive patients receiving AHT. AHT after RP may be considered as an effective treatment for patients with high-risk localized and locally advanced prostate cancer in China although it is recommended only for pN+ by current European Association of Urology (EAU) Guidelines [ 39 , 40 ]. Moreover, in China, quite a few patients choose to receive AHT instead of adjuvant radiotherapy because of the fear of complications of radiotherapy.…”
Section: Discussionmentioning
confidence: 99%